Porous superparamagnetic activated carbon from biomass: Adsorption behaviour and regeneration performance for 2,4-dichlorophenoxyacetic acid removal - H. Sridevi; Ramesh Vinayagam; Raja Selvaraj (PLoS ONE, 2026)
This research used Tabebuia aurea leaves to develop a porous magnetic activated carbon (TA-MAC) that helps to remove 2,4-dichlorophenoxyacetic acid. BET analysis revealed a high specific surface area of 996.87 m 2 /g, while magnetic characterization confirmed the superparamagnetic nature of the adsorbent with a saturation magnetization of 3.89 emu/g, enabling easy magnetic separation after treatment. XPS analysis verified the successful adsorption of 2,4-D through changes in surface elemental composition and functional groups. The optimum adsorption conditions were achieved at pH 2 using a TA-MAC dosage of 0.5 g/L, initial 2,4-D concentration of 50 mg/L, contact time of 120 min, temperature of 303 K, and agitation speed of 150 rpm, resulting in a maximum 2,4-D removal efficiency of 79.52%. Adsorption kinetics followed the pseudo-second order model, indicating the involvement of multiple surface interactions. The maximum adsorption capacity reached 165.18 mg/g at 303 K according to the Langmuir model. Thermodynamic evaluations further supported the physisorption nature of the interaction and confirmed its exothermic character. Additionally, the adsorbent exhibited good regeneration capacity after five cycles. TA-MAC maintained high and consistent performance, achieving over 70% 2,4-D removal efficiency in all tested real water samples, demonstrating its potential for practical applications. Collectively, these findings emphasize the efficacy of the synthesized adsorbent as a practical and sustainable solution for pollution remediation.